Diffraction physics - Cowley, J. M. (John Maxwell), 1923- (North-Holland personal library., 1995)
The first edition of this highly successful book appeared in 1975 and evolved from lecture notes for classes in physical optics, diffraction physics and electron microscopy given to advanced undergraduate and graduate students. The book deals with electron diffraction and diffraction from disordered or imperfect crystals and employed an approach using the Fourier transform from the beginning instead of as an extension of a Fourier series treatment. This third revised edition is a considerably rewritten and updated version which now includes all important developments which have taken place in recent years.